IMPLEMENTASI FRAMEWORK LARAVEL FILAMENT PADA SISTEM CRM UNTUK OPTIMALISASI DATA PELANGGAN DAN PROGRAM LOYALITAS POIN DI TOKO BRANDING TELEMARCO - Edi Sudarsono; M Yazed Vebriandi (Journal of Innovation And Future Technology, 2025)
Web-based customer relationship management (CRM) systems offer modern solutions to enhance customer loyalty through improved data management and transactional point programs. This study focuses on developing a CRM system tailored for TELEMARCO-branded stores under PT. Cahaya Mulia Glassindo Lestari using the Laravel Filament framework. The development process adopts the waterfall model, encompassing requirements analysis, system design, implementation, testing, and maintenance. The system features functionalities for customer data input, transaction recording, and automated point accumulation based on predefined rules. Extensive testing indicates that the CRM system significantly enhances efficiency in managing customer data, improves the precision of point calculations, and provides a user-friendly interface. Additionally, the implementation demonstrates a positive influence on customer retention and strengthens TELEMARCO’s marketing strategies by fostering personalized customer engagement. The adoption of the Laravel Filament framework proves effective due to its responsive design and ease of use, enabling the rapid deployment of web-based applications. This research highlights the practical benefits of integrating modern PHP frameworks in CRM development, particularly for retail businesses seeking to optimize customer relationship processes. Overall, this study contributes to the growing body of knowledge on CRM system advancements, offering a scalable and efficient solution for improving customer loyalty in competitive market environments.